AN IMMIGRANT-FRIENDLY SCHOOL ACCORDING_x000D_ TO THE VIEWS OF STUDENTS, TEACHERS AND_x000D_ PRINCIPALS - ALPAYDIN, YUSUF (My University, 2021)
The aim of this research is to detect the problems that immigrant students experience during adaptation process; to demonstrate efforts made in the adaptation process to school and society and to provide a definition for immigrant-friendly school while also listing the qualities of this school. To achieve that objective,_x000D_ qualitative research method was adopted and via administering phenomenological approach, participants’ views were analyzed in-depth. Semi-structured_x000D_ interview questions designed by researchers themselves were used as data collection tool. Population was determined through purposeful sampling method._x000D_ The group consists of 8 immigrant students studying in high school grade during_x000D_ 2020-2021 academic year in Beykoz district of İstanbul city; 5 principals from_x000D_ high schools where immigrant students study and similarly 5 high school teachers having taught in immigrant students’ lessons. Descriptive analysis method_x000D_ was administered to obtained data. Attained findings were examined within_x000D_ the framework of the theory of organizational socialization and interpreted by_x000D_ conducting immigrant-friendly city and immigrant-friendly hospital analogies._x000D_ According to these findings during adaptation process immigrant students were_x000D_ exposed to academic, social, cultural and domestic(family-related) problems,_x000D_ and that immigrant-friendly schools put efforts in academic, social, cultural and_x000D_ parental support categories by harnessing varied organizational socialization tactics. Accordingly, immigrant-friendly school concept has been defined as; “an_x000D_ academic institution which-by making efforts needed- in academic, social, cultural support and parental support categories, expediting immigrant students’_x000D_ and their parents’ adaptation to school and society”. According to findings, qualities of an immigrant-friendly school are; enabling social participation, cultural_x000D_ interaction, facilitating access, financial assistance, family participation; offering_x000D_ academic support, psychological support; welcoming immigrant students and_x000D_ equality.

Bu araştırmanın amacı; göçmen öğrencilerin uyum sürecinde yaşadıkları_x000D_ sorunları tespit etmek, okula ve topluma uyumları sürecinde gerçekleştirilen çabaları ortaya koymak ve böylece göçmen dostu okul tanımını yaparak, bu okulun_x000D_ özelliklerini belirlemektir. Bu doğrultuda nitel araştırma yöntemi benimsenmiş_x000D_ olup, katılımcıların görüşleri fenomonolojik bir yaklaşımla derinlemesine analiz_x000D_ edilmiştir. Veri toplama aracı olarak, araştırmacılar tarafından hazırlanan yarı yapılandırılmış görüşme soruları kullanılmıştır. Çalışma grubu; amaçlı örnekleme_x000D_ yöntemiyle belirlenmiş olup, 2020-2021 eğitim öğretim yılında İstanbul ili Beykoz ilçesinde lise kademesinde öğrenim görmekte olan 8 göçmen öğrenci, göçmen öğrencisi bulunan lise kademesi okullardan 5 yönetici ve benzer şekilde lise_x000D_ kademesinde göçmen öğrencilerin derslerine girmiş 5 öğretmenden oluşmaktadır. Elde edilen verilerin incelenmesinde betimsel analiz yöntemi kullanılmıştır._x000D_ Bulgular örgütsel sosyalizasyon teorisi çerçevesinde değerlendirilmiş, göçmen_x000D_ dostu şehir ve göçmen dostu hastane analojileri yapılarak yorumlanmıştır. Bulgulara göre göçmen öğrenciler uyum sürecinde akademik, sosyal, kültürel ve_x000D_ ailevi sorunlarla karşılaşmakta, göçmen dostu okullar ise çeşitli örgütsel sosyalizasyon taktiklerini kullanarak akademik, sosyal, kültürel destek ve ebeveyn desteği kategorilerinde çaba göstermektedirler. Bu doğrultuda göçmen dostu okul_x000D_ kavramı; “akademik, sosyal, kültürel destek ve ebeveyn desteği kategorilerinde_x000D_ gereken çabaları göstererek göçmen öğrencinin ve ebeveynin okula ve topluma_x000D_ uyumunu kolaylaştıran eğitim örgütleri” olarak tanımlanmıştır. Bulgulara göre_x000D_ göçmen dostu okulların özellikleri; sosyal katılım, kültürel etkileşim, erişimi kolaylaştırma, ekonomik destek, aile katılımı sağlama, akademik destek, psikolojik_x000D_ destek, göçmen öğrenciyi kabul, eşitlik şeklindedir
ÖĞRENCİ, ÖĞRETMEN VE OKUL MÜDÜRLERİNİN GÖRÜŞLERİNE GÖRE GÖÇMEN DOSTU OKUL